Journey from social media audience to fashion consumer - Khong Hun, Anjanette O. (College of Home Economics, University of the Philippines Diliman, 2023)
Social media influencer marketing is an emerging marketing strategy that increase brand exposure and drives sales of fashion brands through fashion social media influencers (FSMI). Aside from the fashion brand and FSMI as elements of social media influencer marketing, the audience is another key element, since they ultimately make the purchasing decisions. Despite this, most scholarly works focus on the perspective of the marketer and not the consumers. Thus, this paper puts forward the concept of the “journey from social media audience to fashion consumer” to describe the process of how social media audiences become consumers of fashion brands and products. This occurs when they follow and consume the contents of the FSMIs who feature fashion brands and products. The paper aimed to develop a research proposal by conducting a literature review and crafting a methodology. It is recommended to focus on the “journey” of Generation Z social media audiences who follow Instagram FSMI. The Generation Zs are highly active online and have high disposable income. Instagram is suggested as the social media platform to be studied because its highly visual format is prevalently used in the fashion industry. Furthermore, it is suggested to do a multiple case study approach and to gather data through personal interviews. This will provide in-depth descriptions of the unique experiences of the potential participants in their “journey from social media audiences and fashion consumers” as they follow specific FSMI. A series of pre-tests were conducted to develop an interview guide for the proposed research. The AIDA (attention, interest, desire and action) marketing Model was used as an analytical tool. Through this Model, the respondents in the pretest were able to break down how the FSMIs attracted their attention to learn more about the fashion brand and eventually decided to purchase the product.